Intensification Of Core Streptavidin Production Through High-Cell-Density Cultivation Of Recombinant Escherichia Coli And A Temperature-Based Refolding Method - Chua, Leong Huat (2019)
This study describes the development of an intensified process that enables high level production of recombinant core streptavidin (core SAV), a non-glycosylated tetrameric protein utilised in a wide range of applications. Due to widespread utility and commercial importance of SAV, recombinant SAV production has been studied extensively. However, in most studies, recombinant SAV was expressed in a soluble form, resulting in in vivo sequestration of biotin. Biotin sequestration is detrimental to cell growth and results in low volumetric yield. To improve volumetric yield, in this study, core SAV was expressed as inclusion bodies (IBs) followed by induction at highcell- density. A pH-stat fed-batch feeding strategy was employed to cultivate host cells to high-cell-density, the effect of induction at different cell densities (OD 20, 60 and 100) on volumetric and specific yield were then studied. Highest volumetric yield of core SAV (1.55 g L"1) was obtained from induction at OD 100.